2017
DOI: 10.4081/aiol.2017.7232
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting dynamics and environmental controls of dispersed bacteria along a hydrologic gradient

Abstract: Freshwater bacterioplankton communities are influenced by the transport of bacteria from the surrounding terrestrial environments. It has been shown that, although most of these dispersed bacteria gradually disappear along the hydrologic continuum, some can thrive in aquatic systems and become dominant, leading to a gradual succession of communities. Here we aimed at exploring the environmental factors driving the structure of such contrasting bacterial populations as well as their functional properties. Using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 38 publications
2
15
0
Order By: Relevance
“…Previous studies reported the directional structuring of BCC along the gradient of the river continuum, with a loss of abundant taxa from headwaters and a decreased taxonomic richness downstream (Ruiz‐González, Niño‐García, Berggren, & del Giorgio, ; Ruiz‐González et al., ). Here, we found that the flood pulse controlled not only the transport downstream, but also lateral exchange between the main river (Solimões) and the associated floodplain lake (Janauacá).…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies reported the directional structuring of BCC along the gradient of the river continuum, with a loss of abundant taxa from headwaters and a decreased taxonomic richness downstream (Ruiz‐González, Niño‐García, Berggren, & del Giorgio, ; Ruiz‐González et al., ). Here, we found that the flood pulse controlled not only the transport downstream, but also lateral exchange between the main river (Solimões) and the associated floodplain lake (Janauacá).…”
Section: Discussionmentioning
confidence: 96%
“…However, published studies have generally been limited to either studies of temporal dynamics in one or a few sites or analysis of biogeographical patterns within a single ‘snapshot’ sampling of a broader watershed. A recent study in which 10 streams and rivers were sampled across two seasons found similar trends of decreasing bacterial richness and selective enrichment of Betaproteobacteria , Actinobacteria and Cyanobacteria with increasing distance from headwaters (Ruiz‐González et al ., ). However, a study of the Kalamas river in Greece (Meziti et al ., ) found extensive temporal variation in community composition and in the relative abundance of bacteria from different source environments, suggesting that the community assembly process may be sensitive to temporal variation in hydrologic regime, water physicochemical conditions and/or the composition of source communities.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have addressed bacterial community diversity within the water columns of large rivers (Ruiz-González et al, 2013;Jackson et al, 2014;Kolmakova et al, 2014;de Oliveira and Margis, 2015;Savio et al, 2015;Staley et al, 2015), within stream networks (Read et al, 2015;Ruiz-González et al, 2015;Niño-García et al, 2016b;Ruiz-González et al, 2017) and among the benthic biofilms of streams (Besemer et al, 2005;Lear et al, 2013;Wilhelm et al, 2013;Heino et al, 2014). While some studies have found taxonomic shifts closely related to seasonality and physicochemical parameters (Hu et al, 2014;Staley et al, 2015), many have found overall patterns of decreasing diversity along the flow path of the river (Read et al, 2015;Savio et al, 2015) or within a watershed (Crump et al, 2007;Ruiz-González et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The adjusted regression coefficient is 0.54. [Color figure can be viewed at wileyonlinelibrary.com] responses to drought (Drenovsky et al, 2010;Ruiz-González et al, 2018). As previously reported, streambed sediments are completely exposed to the atmosphere under persistent dry conditions and may acquire characteristics similar to those of the adjacent soils (Steward et al, 2012;Morandi et al, 2014;Arce et al, 2019).…”
Section: Discussionmentioning
confidence: 80%
“…The microbial community composition differs between flowing and intermittent sites whereas bacterial diversity and density respond to the environmental features of the catchment area, such as riparian vegetation cover and agricultural land use. Generally, reduced microbial activity, diversity changes and shifts in community composition are expected as the dry period lengthens (Rees et al ., ; Amalfitano and Fazi, ; Marxsen et al ., ), although co‐occurring environmental factors are also often cited as important modulators for microbial responses to drought (Drenovsky et al ., ; Ruiz‐González et al ., ). As previously reported, streambed sediments are completely exposed to the atmosphere under persistent dry conditions and may acquire characteristics similar to those of the adjacent soils (Steward et al ., ; Morandi et al ., ; Arce et al ., ).…”
Section: Discussionmentioning
confidence: 97%